Dinoflagellate cysts in ballast sediments: differences between Canada's east coast, west coast and the Great Lakes. Issue 2 (11th December 2012) - Casas‐Monroy, Oscar; Roy, Suzanne; Rochon, André
ABSTRACT The abundances and diversity of dinoflagellate cysts (including non‐indigenous or harmful species) in ballast sediments were examined for the east and west coasts and the Great Lakes, to assess the potential invasion risk for these organisms and to determine similarity across regions. In total, 147 ships were sampled, distributed among three categories: (1) transoceanic, with mandatory ballast water exchange (BWE); (2) coastal with BWE; and (3) coastal without BWE. Factors that could account for variability in results were examined including ship routes, BWE, ballast water age and sediment volume in ballast tanks. The pattern of potential invasion risk differs according to the region examined. The east coast had greater concentrations of viable cysts per tank, particularly for coastal ships (with a maximum close to 2 × 106 cysts per tank in coastal exchanged ships compared with 1 × 105 for the west coast). When considering viable cysts g‐1 dry sediment, maximum concentrations were found in unexchanged coastal ships from the east coast (28 cysts g‐1 compared with 5 for the west coast), but these ships contained less sediment, decreasing the overall abundance of cysts per tank. These results are in the lower range of values reported for Scotland or Australia, which reached a maximum of 2.3 × 104 cysts cm−3 of sediment. Ballast water exchange had a different influence according to the region: on the east coast, the invasion risk was reduced by BWE while it had no significant effect in the other two regions. Ballast water age and sediment volume were also different among regions, but they were not clearly related with cyst concentrations in ballast tanks. Future management of ballast sediment should take into consideration these regional differences in order to reduce the introduction of dinoflagellate NIS that threaten the conservation of coastal habitats through reduction of native diversity. Copyright © 2012 John Wiley & Sons, Ltd.